Oceanic emissions of dimethyl sulfide and methanethiol and their contribution to sulfur dioxide production in the marine atmosphere - G. A. Novak; G. A. Novak; G. A. Novak; D. B. Kilgour; C. M. Jernigan; M. P. Vermeuel; M. P. Vermeuel; T. H. Bertram (Atmospheric Chemistry and Physics, 2022)
Oceanic emissions of dimethyl sulfide (CH3SCH3, DMS) have long been recognized to impact aerosol particle composition and size, the concentration of cloud condensation nuclei (CCN), and Earth's radiation balance. The impact of oceanic emissions of methanethiol (CH3SH, MeSH), which is produced by the same oceanic precursor as DMS, on the volatile sulfur budget of the marine atmosphere is largely unconstrained. Here we present direct flux measurements of MeSH oceanic emissions using the eddy covariance (EC) method with a high-resolution proton-transfer-reaction time-of-flight mass spectrometer (PTR-ToFMS) detector and compare them to simultaneous flux measurements of DMS emissions from a coastal ocean site. Campaign mean mixing ratios of DMS and MeSH were 72 ppt (28–90 ppt interquartile range) and 19.1 ppt (7.6–24.5 ppt interquartile range), respectively. Campaign mean emission fluxes of DMS (FDMS) and MeSH (FMeSH) were 1.13 ppt m s−1 (0.53–1.61 ppt m s−1 interquartile range) and 0.21 ppt m s−1 (0.10–0.31 ppt m s−1 interquartile range), respectively. Linear least squares regression of observed MeSH and DMS flux indicates the emissions are highly correlated with each other (R2=0.65) over the course of the campaign, consistent with a shared oceanic source. The campaign mean DMS to MeSH flux ratio (FDMS:FMeSH) was 5.5 ± 3.0, calculated from the ratio of 304 individual coincident measurements of FDMS and FMeSH. Measured FDMS:FMeSH was weakly correlated (R2=0.15) with ocean chlorophyll concentrations, with FDMS:FMeSH reaching a maximum of 10.8 ± 4.4 during a phytoplankton bloom period. No other volatile sulfur compounds were observed by PTR-ToFMS to have a resolvable emission flux above their flux limit of detection or to have a gas-phase mixing ratio consistently above their limit of detection during the study period, suggesting DMS and MeSH are the dominant volatile organic sulfur compounds emitted from the ocean at this site.